Reclaiming the Sexed Body: a Reading of Arcangela Tarabotti’s Innocence Betrayed (La semplicità ingannata) - Gabrielli, Francesca Maria (2010)
This paper investigates the subtle ways in which Arcangela Tarabotti, claustrated in the name of her sex and disability, reclaims female embodiment, both disabled and enabled, in her posthumously published protofeminist treatise Innocence Betrayed (La semplicità ingannata). The seventeenth-century prolific polemicist not only questions both the forced monachization of women with disabilities and the cultural devaluation of the body sexed female, but also articulates, in her re-symbolization of biblical women, a heterogeneous “figuration” (Braidotti) of feminine subjectivity, one that endorses the social proliferation of multiple female embodiments as “bodies that matter” (Butler).
Projekt MZOS
ENG